Gretchen Groundhog, it's your day! - Levine, Abby (Albert Whitman, 1998)
When she has to take over the job of appearing in Piccadilly on Groundhog Day to look for her shadow, Gretchen Groundhog is worried and nervous and threatens not to come out.